THE ENTREPRENEURIAL RESILIENCE STUDY ON THE YOUNG NASCENT ENTREPRENEURS - Dimitri Marcello Santoso; Yuanita Ratna Indudewi (Jurnal Manajemen dan Kewirausahaan, 2022)
Changes occur in human existence, particularly in lifestyle, during this pandemic. Changes occur in the workplace on a daily basis. Workers and companies are facing difficulties in surviving the pandemic. The purpose of this study was to assess the link between entrepreneurial self-efficacy, entrepreneurial passion, and entrepreneurial resilience in young nascent entrepreneurs during the COVID-19 pandemic. There were 216 sampels of young nascent entrepreneurs of age 19 to 22 to support this research. SPSS Software was used for data analysis and processing. The result showed during the pandemic, the entrepreneurial self-efficacy variable had a positive significant influence on the entrepreneurial resilience, and the entrepreneurial passion had a positive significant influence on the entrepreneurial resilience. Based on the study and analysis, hypotheses 1 and hypothesis 2 were accepted since they had a substantial effect on the entrepreneurial resilience variable, either partially or simultaneously. During the pandemic, a young nascent entrepreneur needed to remain inventive and able to create opportunities in operating their businesses. Further study on other aspects that can affect entrepreneurial resilience was adviseable.